Strain attribution of Ukrainian isolates of Zucchini yellow mosaic virus and their occurrence in Ukraine - Tsvigun, V.O.; Rudneva, T.O.; Shevchenko, T.P.; Budzanivska, I.G.; Polishchuk, V.P. (Вiopolymers and Cell, 2016)
Aim. Establishing the strain attribution of Ukrainian isolates of Zucchini yellow mosaic virus ZYMV and their occurrence in Ukraine. Methods. Visual examination, DAS-ELISA, RT-PCR, DNA sequencing, and phylogenetic analysis. Results. Plants from Cucurbitaceae family were checked for the presence of ZYMV antigens. DAS-ELISA showed that 41 % of examined cucurbit plants were infected by ZYMV. The infected plants were detected in agroecosystems of Vinnytsia, Zaporizhzhia, Kyiv, Poltava and Cherkasy regions. cDNA of 605 bp corresponding to the Nib/CP genome region of ZYMV was obtained using RT-PCR. Phylogenetic analysis of the nucleotide sequence of the Nib/CP region of Ukrainian isolates was conducted. Conclusions. The identification of infected plants in 5 of 9 inspected agroecosystems suggests a high prevalence of the ZYMV infection in Ukraine. The topology of a reconstructed phylogenetic tree confirmed the previously established clustering of ZYMV isolates into three groups. The phylogenetic positioning of the Ukrainian ZYMV isolates on this tree demonstrates that they belong to a subgroup I of group A. This group is the most numerous group, which consists of members of different geographic origins. The ZYMV isolates circulating in Ukraine were found to be nearly identical: their levels of pairwise identity range from 99.7 to100. They have a monophyletic origin with the European isolates from Austria (AJ420017), Slovenia (AJ420018), Serbia (HM072432), Hungary (AJ459955), Slovakia (DQ124239). The levels of pairwise identity between the Ukrainian and European isolates range from 94.3 to 100 %.